Characterizing patient details-related challenges from health information technology-related incident reports from Swedish healthcare - Jabin, Md Shafiqur Rahman; Pan, Ding; Nilsson, Evalill (Frontiers in Digital Health, 2024)
Introduction: Despite many benefits offered by Health Information Technology (HIT) systems, new technology brings new and unforeseen risks to healthcare quality and patient safety if they're not properly planned, designed, implemented, and managed. This study examined health information technology-related (HIT) incidents to identify patient details-related issues, their association with contributing factors, and outcomes.Methods: Sources of information comprised retrospectively collected incident reports (n=95) using two sampling methods, i.e., purposive and snowball sampling. The incident reports were analyzed using both the inductive method (thematic analysis) and the deductive approach using an existing framework, i.e., the International Classification for Patient Safety.The studies identified 90 incidents with 120 patient details-related issues-categorized as either information-related (48%) or documentation-related (52%) problems; around two-thirds of the 120 issues were characterized by human factors. Of the total sample, 87 contributing factors were identified, of which "medical device/system" (45%) and "documentation" (20%) were the most common contributing factors. Of 90 incidents, more than half (59%) comprised patient-related outcomes-patient inconvenience (47%) and patient harm (12%) and the remaining 41% (n=37) included staff or organization-related outcomes.Discussion: More than half of the incidents resulted in patient-related outcomes, namely patient inconvenience and patient harm, including disease risks, severe health deterioration, injury, and even patient death. Incidents associated with patient details can cause deleterious effects; therefore, characterizing them should be a routine part of clinical practice to improve the constantly changing healthcare system.